Self-assembled vesicles of urea-tethered foldamers as hydrophobic drug carriers - Ingole, Tukaram S.; Kale, Sangram S.; Sukumaran, Santhosh Babu; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
Molecular self-assembly of nonamphiphilic alpha,beta-hybrid foldamers based on urea-tethered anthranilic acid-proline (Ant-Pro) foldamers is reported. These self-assembled hollow vesicular architectures can take up and release the anticancer hydrophobic drug curcumin.